Next-Gen Surgery: AI Robots Leading the Way in Healthcare - Aisha, Saman (Archives of Community Medicine and Public Health, 2024)
As human generations evolve, medical science and engineering have developed, and robotics have become an integral part of medicine from administrative duties to surgical procedures. In medical procedures, robotic systems support and enhance the accuracy and agility of human surgeons. This method is known as robotic surgery or robotic-assisted surgery (RAS). In the public health field, RAS plays an essential role due to its ability to improve surgical precision, lessen patient discomfort following surgery, and shorten hospital stays. In spite of the systems not being entirely self-contained, skilled surgeons use a console and specialized instruments to perform procedures that are more accurate and less invasive. Robots can help provide healthcare services such as monitoring vital signs, administering medications, and providing emotional support. The use of AI with robotics in healthcare has shown a remarkable rise in the past few years, particularly in rural India with limited access to healthcare providers and limited health resources. Urban and rural hospitals across the country can use artificial intelligence to manage tasks like surgery assistance, streamlining hospital logistics, and organizing routine checkups. The following considerations are the main causes of a surge in robotic help in the healthcare sector: (a) robots are hardworking; (b) they can withstand stress; (c) their grasping abilities; (d) they can do precise surgeries; and (e) they are capable of performing repetitive jobs. The present discourse delves into a few medical robotics applications, discussing their advantages, disadvantages, and possible avenues for future research and development.